Extraction of Cobalt and Manganese from Ferromanganese Crusts Using Industrial Metal Waste through Leaching - Kevin Pérez; Norman Toro; Pedro Robles; Felipe M. Galleguillos Madrid; Edelmira Gálvez; Francisco Javier González; Egidio Marino; Jonathan Castillo; Ingrid Jamett; Pía C. Hernández (Metals)
Ferromanganese crusts are mineral resources distributed in the planet’s oceans. These deep-sea minerals stand out for their abundance and diversity of metals, with Mn and Co being the most abundant elements. These minerals are a good alternative to diversify the extraction of elements, which today are found at low grades on the Earth’s surface. For the co-processing of ferromanganese crusts to recover Co and Mn, there are few studies. These generally worked with the use of a reducing agent, and in many cases previous roasting processes. In the present investigation, two ferromanganese crusts that were collected from two seamounts in the central eastern Atlantic Ocean were characterized. Subsequently, these crusts were leached in an acid-reducing medium, adding steel waste (slag) with 99.73% Fe3O4 and 0.27% metallic iron from the steel industry as a reducing agent. Acid-reducing processes have previously been shown to yield high and rapid recoveries of Co and Mn from seabed minerals. However, there is no previous study using smelting slag as a reducing agent for the treatment of ferromanganese crusts. The best results of this research were obtained when working at 60 C, achieving joint extractions of Co and Mn of ~80% and ~40%, respectively, in 10 min. In addition, the process residues were analyzed, and the formation of contaminating elements or the precipitation of Co and Mn species was not observed.